STUDI LITERATUR: PERAN MEDIA PEMBELAJARAN BERBASIS DIGITAL DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI ERA KURIKULUM MERDEKA - Ely Yuliawan; Dinda S; Muhammad Bintang Dzikri; Riski Tama Candra; Rahmad Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of digital-based instructional media in Physical Education learning within the context of the Merdeka Curriculum through a literature review of ten national scholarly journals. The analysis focuses on previous findings related to the effectiveness of instructional videos, interactive multimedia, digital applications, learning platforms, and educational games in supporting Physical Education learning. The results indicate that digital media enhance students’ interest and engagement, provide clearer visualization of movement, strengthen motor skills, and offer more efficient and authentic assessment methods. Furthermore, digital media support flexible and adaptive learning in alignment with the principles of the Merdeka Curriculum. Nevertheless, challenges such as limited technological facilities, internet access, and teachers’ digital literacy remain obstacles that require systematic attention. Overall, the integration of digital media holds significant potential to improve the quality of Physical Education learning when supported with adequate infrastructure and teacher competence.